A calcium silicate board prepared by using calcium silicate fiber crystals and a preparation method thereof
The preparation of high-strength calcium silicate fiber crystals through hydrothermal reaction method solves the problems of high energy consumption and high cost in the production process of calcium silicate boards, and realizes the preparation of lightweight and high-strength calcium silicate boards, which is safe and environmentally friendly.
Patent Information
- Application Number
- CN202310295053.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-22
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2043-03-22
AI Technical Summary
The existing calcium silicate boards have high energy consumption and high cost problems during the production process, and traditional reinforced fibers such as pulp fibers and asbestos fibers have safety and environmental risks.
High-strength calcium silicate fiber crystals (hard silicate) were prepared by hydrothermal reaction method. The fiber crystals have good thermal stability, high aspect ratio, excellent mechanical properties, and are compatible with the raw materials of calcium silicate boards. They are easy to disperse evenly and play a role in strengthening muscles and bones.
By using calcium silicate fiber crystals, the production cost of calcium silicate boards is reduced, the mechanical properties and safety of the boards are improved, and energy consumption is reduced, making them suitable for large-scale applications.
Smart Images

Figure CN116239361B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of inorganic plates, and in particular relates to a calcium silicate board prepared by using calcium silicate fiber crystals and a preparation method thereof. Background Art
[0002] With the implementation of GB50222-2017 "Code for Fire Protection Design of Building Interior Decoration", the fire protection requirements for building materials are becoming increasingly stringent, the market competition is becoming more and more fierce, and higher requirements are also placed on the performance of panels.
[0003] Calcium silicate board is a new type of energy-saving board made of calcium source, silicon source, reinforcing fiber and functional additives in a certain proportion, using the copying method or slurry method, pre-curing, autoclaving and other processes. It can be used in many fields such as walls, ceilings, and floors. During the autoclaving process, the calcium source and the silicon source react to form calcium silicate hydrate. As the steam curing time and the steam curing temperature increase, the calcium silicate hydrate will change from an amorphous structure to tobermorite crystals or hard-to-morite crystals. Among them, the steam curing temperature for the formation of hard-to-morite crystals needs to exceed 200°C, and the energy consumption required is very high. In actual production, in order to reduce energy consumption, the steam curing temperature of calcium silicate board is usually 180-200°C, and the strength phase crystals inside the board are mainly amorphous calcium silicate hydrate and some tobermorite. Since amorphous calcium silicate hydrate has poor strength, it is necessary to add additional materials such as pulp fiber and cement to improve the mechanical properties of calcium silicate board. However, the price of pulp fiber is expensive, which will significantly increase the cost of board making. However, the high density of cement materials will result in heavy board density, which is not conducive to production and transportation.
[0004] Therefore, selecting a suitable process formula, reducing the production cost (raw material cost and energy consumption cost) of calcium silicate board, and preparing lightweight and high-strength calcium silicate board products are of great significance for the large-scale application of calcium silicate board.
[0005] Patent CN202210529467.X discloses a preparation method of calcium silicate board and calcium silicate board, wherein slurry slag, cement, reinforcing fiber, perlite, fly ash, asbestos and water are mixed to form a slurry, and the slurry is formed by a slurry flow method. This method introduces asbestos as a reinforcing material to replace the use of part of the reinforcing fiber, which can effectively reduce the cost of the board and improve the mechanical properties of the board, but asbestos will cause harm to the safety and health of personnel during construction and use.
[0006] Patent CN113998933 A discloses a calcium silicate board and its preparation method, wherein iron oxide green, dispersant and water are mixed to obtain a mixed liquid, white material, tailings and stone powder are mixed to obtain a mixture, and then the mixed liquid and the mixed material are mixed to obtain a wet material, and the calcium silicate board is obtained through pressing, drying and carbonization. This method uses white material, tailings and stone powder to reduce the raw material cost of the calcium silicate board, and replaces autoclave curing with vacuum CO2 carbonization to reduce energy consumption. This method can significantly improve the mechanical properties of the calcium silicate board, but the cost of vacuum CO2 carbonization is relatively high, and it has not yet been widely popularized among calcium silicate board manufacturers. Summary of the invention
[0007] In order to reduce the production cost of calcium silicate board, obtain light and high-strength calcium silicate board products, and at the same time minimize the technical transformation cost of calcium silicate manufacturers, the present invention provides a calcium silicate board prepared by using calcium silicate fiber crystals and a preparation method thereof. A high-strength calcium silicate fiber crystal (hard calcium silicate, 6CaO·6SiO2·H2O) is prepared by hydrothermal reaction of a high-quality calcium source and a high-quality silicon source. The calcium silicate fiber crystal has the characteristics of good thermal stability, high aspect ratio, excellent mechanical properties, and non-toxicity. As a reinforcing fiber in the raw material of calcium silicate board, compared with pulp fiber, polyvinyl alcohol fiber, and asbestos fiber, the calcium silicate fiber crystal and the strength phase of the calcium silicate board (amorphous hydrated calcium silicate and tobermorite) belong to the same calcium silicate class, so it has better compatibility with the calcium silicate board, is easy to disperse evenly, and plays a role in strengthening muscles and bones. It has a significant effect on improving the mechanical properties of the calcium silicate board, and provides ideas for preparing a light and high-strength calcium silicate board.
[0008] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0009] A method for preparing a calcium silicate board using calcium silicate fiber crystals, specifically comprising the following steps:
[0010] (1) selecting a high-quality silicon source, a high-quality calcium source and water, mixing and stirring, and performing a hydrothermal reaction at a temperature of 200 to 240° C. and a pressure of 1.5 to 3.3 MPa; after the hydrothermal reaction is completed, the product is post-treated to obtain calcium silicate fiber crystals;
[0011] (2) After mixing a common silicon source, a common calcium source, gypsum, cement, an inorganic filler and water evenly, adding calcium silicate fiber crystals, and mixing them evenly together to obtain a slurry;
[0012] (3) injecting the slurry into a mold and pre-curing to obtain a pre-cured sample; then placing the pre-cured sample in a steam curing kettle for autoclave curing; after the autoclave curing is completed, drying, sanding, and cutting the steam-cured sample to obtain a calcium silicate board.
[0013] In the step (1), the high-quality silicon source is white silica ash, and the mass content of SiO2 in the white silica ash is not less than 95%; the high-quality calcium source in the step (1) is calcium oxide, and the purity of calcium oxide is not less than 90%; the molar ratio of SiO2 in the high-quality silicon source to CaO in the high-quality calcium source is 1 to 1.2, and the mass ratio of the total mass of the high-quality silicon source and the high-quality calcium source to water is 1:15 to 30.
[0014] The hydrothermal reaction time in step (1) is 3 to 6 hours, and the stirring rate is 400 to 800 rpm.
[0015] The common calcium source in step (2) is one or a combination of calcium silicate slag, carbide slag, quicklime and slaked lime.
[0016] In the step (2), the common silicon source is one or a combination of calcium silicate slag, microsilica powder, silicon micropowder, and quartz sand.
[0017] The inorganic filler in step (2) is one or a combination of diatomaceous earth, bentonite and fly ash.
[0018] The weight fractions of the raw material components in step (2) are as follows, wherein the common silicon source is weighed according to the weight content of SiO2, and the common calcium source is weighed according to the weight content of the calcium compound therein:
[0019] 25-35 parts of SiO2 in common silicon source, 24-30 parts of CaO in common calcium source, 8-15 parts of gypsum, 8-15 parts of cement, 5-30 parts of calcium silicate fiber crystals, 3-8 parts of inorganic filler, and 250-500 parts of water.
[0020] In the step (3), the pre-curing temperature is 50-60° C. and the time is 4-8 hours.
[0021] In the step (3), the autoclave curing temperature is 180-200° C., the pressure is 1-1.5 MPa, and the autoclave curing time is 8-16 hours.
[0022] The calcium silicate fiber crystal belongs to inorganic materials, is easy to mix evenly with the raw materials of calcium silicate board, and is evenly dispersed in the calcium silicate board. Its main body belongs to xonotlite crystal phase, has stable chemical properties, excellent mechanical properties, can be closely combined with the strength phase (amorphous hydrated calcium silicate and tobermorite) of calcium silicate board, plays the role of strengthening muscles and bones, and replaces reinforcing fibers such as paper pulp. At the same time, some active sites of the calcium silicate fiber crystal can stimulate the hydration reaction of common calcium source and common silicon source in the raw material of calcium silicate board, act as "seed", play an inductive role, accelerate the reaction of common calcium source and common silicon source in the raw material to form a higher crystallinity calcium silicate crystal phase, thereby improving the mechanical properties of calcium silicate board. Therefore, under the premise of ensuring that the calcium silicate board is light and high-strength, the present invention can select silicon and calcium industrial solid wastes with general reaction activity as board making raw materials, thereby reducing the production cost of calcium silicate board.
[0023] In order to ensure that the calcium silicate fiber crystal in the present invention has a high application value, the process parameters of its preparation are extremely important. The temperature is too low, the strength of the obtained crystal is poor, and there is an amorphous calcium silicate hydrate structure, which leads to a decrease in the strengthening effect of muscles and bones. If the temperature is too high, it will bring about an increase in energy consumption, resulting in an increase in production costs. At the same time, the reaction time will also affect its molding. The reaction time is too short, and high-quality calcium sources and high-quality silicon sources mainly exist in amorphous calcium silicate hydrate structures or tobermorite structures, and the thermal stability of the two is poor, and the strengthening effect of muscles and bones is weak. The reaction time is too long, and the fibrous hard calcium silicate crystals will be intertwined and interwoven with each other to form hollow spherical hard calcium silicate secondary crystals, resulting in high production energy consumption and poor dispersibility.
[0024] Compared with the prior art, the beneficial effects of the present invention are as follows
[0025] 1. Select high-quality calcium source and high-quality silicon source with good hydration activity, and form calcium silicate fiber crystal (i.e., xonotlite, 6CaO·6SiO2·H2O) through hydrothermal reaction. It has the characteristics of good thermal stability, high aspect ratio, excellent mechanical properties, non-toxic and harmless, and is of the same strength as the calcium silicate board (amorphous hydrated calcium silicate or tobermorite). It is easy to disperse evenly and can play a role in strengthening the muscles and bones in the calcium silicate board, thereby improving the flexural strength of the calcium silicate board, and providing a new optimization idea for the preparation of lightweight and high-strength calcium silicate board.
[0026] 2. Calcium silicate fiber crystals are used to replace conventional pulp fibers, asbestos and other reinforcing materials. They are safe, environmentally friendly, harmless to the human body, have excellent mechanical properties, and good thermal stability. The preparation process is simple and can be used on a large scale in calcium silicate boards and even inorganic boards to improve the mechanical properties of the boards.
[0027] 3. The addition of the calcium silicate fiber crystals does not change the production process and equipment of conventional calcium silicate boards, and calcium silicate board products of different specifications can be prepared.
[0028] 4. The calcium silicate board fiber crystals are added to the calcium silicate board, which has a high aspect ratio and a stable chemical structure. They are staggered and overlapped in the calcium silicate board, which can effectively improve the screw holding force of the calcium silicate board and reduce the density of the calcium silicate board, thereby promoting the application of calcium silicate board in the field of decorative panels.
[0029] 5. Increasing the amount of calcium silicate fiber crystals can make the calcium silicate board made from industrial solid wastes such as calcium silicate slag and fly ash meet the product standards, broaden the source of raw materials for calcium silicate boards, and thus reduce their production costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is the crystal morphology of calcium silicate fiber synthesized under hydrothermal conditions using high-quality calcium source and high-quality silicon source in Example 1 of the present invention.
[0031] Figure 2 This is the XRD test result of the calcium silicate fiber crystal synthesized under hydrothermal conditions using high-quality calcium source and high-quality silicon source in Example 1 of the present invention.
[0032] Figure 3 This is the morphology of the calcium silicate fiber crystals in the calcium silicate board in Example 1 of the present invention.
[0033] Figure 4 This is the crystal morphology of calcium silicate synthesized under hydrothermal conditions using a calcium source and a silicon source in Comparative Example 1 of the present invention.
[0034] Figure 5 This is the crystal morphology of calcium silicate synthesized under hydrothermal conditions using a calcium source and a silicon source in Comparative Example 2 of the present invention.
[0035] Figure 6 This is the crystal morphology of calcium silicate synthesized under hydrothermal conditions using calcium source and silicon source in Comparative Example 3 of the present invention.
[0036] Figure 7 This is the crystal morphology of calcium silicate synthesized under hydrothermal conditions using calcium source and silicon source in Comparative Example 4 of the present invention.
[0037] Figure 8 This is the combination of pulp and calcium silicate board in Comparative Example 5 of the present invention. DETAILED DESCRIPTION
[0038] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only some embodiments of the present invention, but not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] Example 1
[0040] The preparation method of calcium silicate fiber crystals and the application thereof in calcium silicate boards described in the present invention comprise the following steps:
[0041] ①, weigh 120g of white silica fume (SiO2 mass content is 95%), 99g of calcium oxide (CaO mass content is 90%), and 4200g of water, place them in a hydrothermal reactor and stir them for reaction at a stirring rate of 400rpm, a temperature of 200℃, a pressure of 1.5MPa, and react for 4h;
[0042] ② After washing and filtering the product of the hydrothermal reaction, place it in an 80°C forced air drying oven and dry it to constant weight to obtain calcium silicate fiber crystals for standby use;
[0043] ③. Weigh 250g of microsilica powder, 343g of carbide slag (including 70% CaO mass content), 80g of gypsum, 80g of cement, 30g of bentonite, 30g of diatomaceous earth, 2500g of water, and 180g of calcium silicate fiber crystals, stir well to obtain calcium silicate board slurry.
[0044] ④. Inject the slurry into a 50cm×50cm mold and place it in a blast oven at 50℃ for pre-curing for 8 hours until the slurry is initially solidified and formed;
[0045] ⑤. The pre-cured sample is placed in a steam curing kettle and cured under the conditions of 180°C and 1MPa for 16 hours to obtain a sample;
[0046] ⑥ The steamed sample is dried, sanded and cut to obtain the calcium silicate board.
[0047] Example 2
[0048] The preparation method of calcium silicate fiber crystals and the application thereof in calcium silicate boards described in the present invention comprise the following steps:
[0049] ①, weigh 240g of white silica fume (SiO2 mass content is 98%), 200g of calcium oxide (CaO mass content is 95%), and 6600g of water, place them in a hydrothermal reactor and stir them for reaction at a stirring rate of 800rpm, a temperature of 200℃, a pressure of 1.5MPa, and react for 4h;
[0050] ② After washing and filtering the product of the hydrothermal reaction, place it in an 80°C forced air drying oven and dry it to constant weight to obtain calcium silicate fiber crystals for standby use;
[0051] ③. Weigh 673g of calcium silicate slag (including 52% CaO mass content and 25% SiO2 mass content), 280g of quartz sand, 150g of gypsum, 150g of cement, 30g of bentonite, 30g of diatomaceous earth, 5000g of water, and 280g of calcium silicate fiber crystals, stir well to obtain calcium silicate board slurry.
[0052] ④. Inject the slurry into a 50cm×50cm mold and place it in a blast oven at 50℃ for pre-curing for 8 hours until the slurry is initially solidified and formed;
[0053] ⑤. The pre-cured sample is placed in a steam curing kettle and cured by autoclave at 200°C and 1.5MPa for 8 hours to obtain a sample;
[0054] ⑥ The steamed sample is dried, sanded and cut to obtain the calcium silicate board.
[0055] Example 3
[0056] The preparation method of calcium silicate fiber crystals and the application thereof in calcium silicate boards described in the present invention comprise the following steps:
[0057] ①, weigh 120g of white silica fume (SiO2 mass content is 95%), 110g of calcium oxide (CaO mass content is 95%), and 6900g of water, place them in a hydrothermal reactor and stir them for reaction at a stirring rate of 600rpm, a temperature of 240℃, a pressure of 3.3MPa, and react for 3h;
[0058] ② After washing and filtering the product of the hydrothermal reaction, place it in an 80°C forced air drying oven and dry it to constant weight to obtain calcium silicate fiber crystals for standby use;
[0059] ③. Weigh 350g of microsilica powder, 429g of carbide slag (including 70% CaO mass content), 150g of gypsum, 150g of cement, 80g of bentonite, 4500g of water, and 300g of calcium silicate fiber crystals, stir well to obtain calcium silicate board slurry.
[0060] ④. Inject the slurry into a 50cm×50cm mold and place it in a blast oven at 60℃ for pre-curing for 4 hours until the slurry is initially solidified and formed;
[0061] ⑤. The pre-cured sample is placed in a steam curing kettle and cured under the conditions of 180°C and 1MPa for 16 hours to obtain a sample;
[0062] ⑥ The steamed sample is dried, sanded and cut to obtain the calcium silicate board.
[0063] Example 4
[0064] The preparation method of calcium silicate fiber crystals and the application thereof in calcium silicate boards described in the present invention comprise the following steps:
[0065] ①, weigh 120g of white silica fume (SiO2 mass content is 95%), 110g of calcium oxide (CaO mass content is 95%), and 3500g of water, place them in a hydrothermal reactor and stir them for reaction at a stirring rate of 400rpm, a temperature of 200℃, a pressure of 1.5MPa, and react for 6h;
[0066] ② After washing and filtering the product of the hydrothermal reaction, place it in an 80°C forced air drying oven and dry it to constant weight to obtain calcium silicate fiber crystals for standby use;
[0067] ③. Weigh 300g of silicon micropowder, 330g of quicklime (including 85% CaO mass content), 120g of gypsum, 120g of cement, 15g of bentonite, 40g of diatomaceous earth, 3500g of water, and 250g of calcium silicate fiber crystals, stir evenly to obtain calcium silicate board slurry.
[0068] ④. Inject the slurry into a 50cm×50cm mold and place it in a blast oven at 50℃ for pre-curing for 4 hours until the slurry is initially solidified and formed;
[0069] ⑤. The pre-cured sample is placed in a steam curing kettle and cured under the conditions of 190°C and 1.25MPa for 12 hours to obtain a sample;
[0070] ⑥ The steamed sample is dried, sanded and cut to obtain the calcium silicate board.
[0071] Comparative Example 1
[0072] The preparation method of calcium silicate fiber crystals and the application thereof in calcium silicate boards described in the present invention comprise the following steps:
[0073] ①, weigh 120g of white silica fume (SiO2 mass content is 95%), 99g of calcium oxide (CaO mass content is 90%), and 4200g of water, place them in a hydrothermal reactor and stir to react at a stirring rate of 400rpm, a temperature of 180℃, a pressure of 2.5MPa, and react for 4h;
[0074] ② After washing and filtering the product of the hydrothermal reaction, place it in an 80°C forced air drying oven and dry it to constant weight to obtain calcium silicate fiber crystals for standby use;
[0075] ③. Weigh 250g of microsilica powder, 343g of carbide slag (including 70% CaO mass content), 80g of gypsum, 80g of cement, 30g of bentonite, 30g of diatomaceous earth, 2500g of water, and 180g of calcium silicate fiber crystals, stir well to obtain calcium silicate board slurry.
[0076] ④. Inject the slurry into a 50cm×50cm mold and place it in a blast oven at 50℃ for pre-curing for 4 hours until the slurry is initially solidified and formed;
[0077] ⑤. The pre-cured sample is placed in a steam curing kettle and cured under the conditions of 180°C and 1MPa for 16 hours to obtain a sample;
[0078] ④. The steamed sample is dried, sanded and cut to obtain the calcium silicate board.
[0079] Comparative Example 2
[0080] The preparation method of calcium silicate fiber crystals and the application thereof in calcium silicate boards described in the present invention comprise the following steps:
[0081] ①, weigh 120g of white silica fume (SiO2 mass content is 95%), 99g of calcium oxide (CaO mass content is 90%), and 4200g of water, place them in a hydrothermal reactor and stir them for reaction at a stirring rate of 400rpm, a temperature of 200℃, a pressure of 2.5MPa, and react for 2h;
[0082] ② After washing and filtering the product of the hydrothermal reaction, place it in an 80°C forced air drying oven and dry it to constant weight to obtain calcium silicate fiber crystals for standby use;
[0083] ③. Weigh 250g of microsilica powder, 343g of carbide slag (including 70% CaO mass content), 80g of gypsum, 80g of cement, 30g of bentonite, 30g of diatomaceous earth, 2500g of water, and 180g of calcium silicate fiber crystals, stir well to obtain calcium silicate board slurry.
[0084] ④. Inject the slurry into a 50cm×50cm mold and place it in a blast oven at 50℃ for pre-curing for 4 hours until the slurry is initially solidified and formed;
[0085] ⑤. The pre-cured sample is placed in a steam curing kettle and cured under the conditions of 180°C and 1MPa for 16 hours to obtain a sample;
[0086] ② The steamed sample is dried, sanded and cut to obtain the calcium silicate board.
[0087] Comparative Example 3
[0088] The preparation method of calcium silicate fiber crystals and the application thereof in calcium silicate boards described in the present invention comprise the following steps:
[0089] ①, weigh 120g diatomaceous earth (SiO2 mass content is 95%), 99g calcium oxide (CaO mass content is 90%), 4200g water, place in a hydrothermal reactor and stir to react, stirring speed is 400rpm, temperature is 200℃, pressure is 2.5MPa, reaction time is 4h;
[0090] ② After washing and filtering the product of the hydrothermal reaction, place it in an 80°C forced air drying oven and dry it to constant weight to obtain calcium silicate fiber crystals for standby use;
[0091] ③. Weigh 250g of microsilica powder, 343g of carbide slag (including 70% CaO mass content), 80g of gypsum, 80g of cement, 30g of bentonite, 30g of diatomaceous earth, 2500g of water, and 180g of calcium silicate fiber crystals, stir well to obtain calcium silicate board slurry.
[0092] ④. Inject the slurry into a 50cm×50cm mold and place it in a blast oven at 50℃ for pre-curing for 4 hours until the slurry is initially solidified and formed;
[0093] ⑤. The pre-cured sample is placed in a steam curing kettle and cured under the conditions of 180°C and 1MPa for 16 hours to obtain a sample;
[0094] ⑥ The steamed sample is dried, sanded and cut to obtain the calcium silicate board.
[0095] Comparative Example 4
[0096] The preparation method of calcium silicate fiber crystals and the application thereof in calcium silicate boards described in the present invention comprise the following steps:
[0097] ①, weigh 120g of white silica fume (SiO2 mass content is 95%), 99g of calcium oxide (CaO mass content is 90%), and 4200g of water, place them in a hydrothermal reactor and stir to react at a stirring rate of 1000rpm, a temperature of 220℃, a pressure of 2.5MPa, and react for 4h;
[0098] ② After washing and filtering the product of the hydrothermal reaction, place it in an 80°C forced air drying oven and dry it to constant weight to obtain calcium silicate fiber crystals for standby use;
[0099] ③. Weigh 250g of microsilica powder, 343g of carbide slag (including 70% CaO mass content), 80g of gypsum, 80g of cement, 30g of bentonite, 30g of diatomaceous earth, 2500g of water, and 180g of calcium silicate fiber crystals, stir well to obtain calcium silicate board slurry.
[0100] ④. Inject the slurry into a 50cm×50cm mold and place it in a blast oven at 50℃ for pre-curing for 4 hours until the slurry is initially solidified and formed;
[0101] ⑤. The pre-cured sample is placed in a steam curing kettle and cured under the conditions of 180°C and 1MPa for 16 hours to obtain a sample;
[0102] ⑥ The steamed sample is dried, sanded and cut to obtain the calcium silicate board.
[0103] Comparative Example 5
[0104] The preparation method of calcium silicate fiber crystals and the application thereof in calcium silicate boards described in the present invention comprise the following steps:
[0105] ①. Weigh 250g of microsilica powder, 343g of carbide slag (including 70% CaO mass content), 80g of gypsum, 80g of cement, 30g of bentonite, 30g of diatomaceous earth, 2500g of water and 180g of pulp, stir well to obtain calcium silicate board slurry.
[0106] ②. Inject the slurry into a 50cm×50cm mold and place it in a blast oven at 50℃ for pre-curing for 4 hours until the slurry is initially solidified and formed;
[0107] ③. The pre-cured sample is placed in a steam curing kettle and cured under the conditions of 180°C and 1MPa for 16 hours to obtain a sample;
[0108] ④. The steamed sample is dried, sanded and cut to obtain the calcium silicate board.
[0109] Performance Testing
[0110] XRD characterization: The calcium silicate crystals obtained in Example 1 were characterized using a Japanese Rigaku Ultima VI, and the results are as follows: Figure 2 As shown, the peak positions of Xonotlite in the PDF cards of the obtained calcium silicate crystals and calcium silicate fiber crystals are the same, that is, the xonotlite structure, and the product has fewer impurity peaks and sharp peaks, indicating that the obtained xonotlite has high crystallinity and low impurity content.
[0111] Morphology test: Zeiss Sigma 300 was used to perform morphology tests on Example 1 and Comparative Examples 1-5. Figure 1 It can be seen that the calcium silicate fiber crystals prepared in Example 1 have a high aspect ratio and a relatively uniform morphology. Figure 3 It can be seen that the added calcium silicate fiber crystals are tightly combined with the calcium silicate board, and the structure of the calcium silicate fiber crystals is well preserved; Figure 4 It can be seen that the calcium silicate prepared in Comparative Example 1 is a spherical short flake structure. Figure 5 It can be seen that the calcium silicate prepared in Comparative Example 2 is a spherical short fiber structure. Figure 6 It can be seen that the calcium silicate crystals obtained in Comparative Example 3 are disordered, and no calcium silicate fibers are obtained. Figure 7 It can be seen that the calcium silicate crystals prepared in Comparative Example 4 are entangled and intertwined with each other to form a hollow spherical structure. Figure 8 It can be seen that the combination of the pulp and the calcium silicate board in Comparative Example 5 is not tight enough.
[0112] Physical and chemical properties test: The bending strength and screw holding force of the calcium silicate boards prepared in Examples 1-4 and Comparative Examples 1-5 were tested using a Haida Universal Mechanical Testing Machine. The results are shown in Table 1:
[0113] Table 1 Physical and chemical properties test of calcium silicate board in Examples 1-4 and Comparative Examples 1-5
[0114]
[0115]
[0116] It can be seen from Example 1 and Comparative Example 1 that the hydrothermal reaction temperature is too low and the formed calcium silicate crystals ( Figure 4 ) is a spherical short-flaked structure, and contains more amorphous hydrated calcium silicate structures at the same time. The chemical stability of this structure is poor, and the hydration reaction will continue during the steaming process of the calcium silicate board. Therefore, the muscle and bone strengthening effect of the calcium silicate board is limited, and the flexural strength is poor. It can be seen from Example 1 and Comparative Example 5 that when industrial solid waste such as carbide slag is used as a raw material, the calcium silicate fiber crystal can have a higher compatibility with the silicon source and calcium source in the plate, and thus the muscle and bone strengthening effect is better than that of paper pulp. At the same time, the active sites on the calcium silicate fiber crystal can also stimulate the calcium source with poor activity in the industrial solid waste to further react with the silicon source to form a calcium silicate product with a crystal structure, thereby improving the strength of the calcium silicate board made of industrial solid waste raw materials. At the same time, in industrial production, the calcium silicate fiber crystal has stable chemical properties, is not easy to absorb water, and is easier to disperse evenly than fibers such as paper pulp.
[0117] It can be seen from Example 1 and Comparative Example 2 that the hydrothermal reaction time is too short and the formed calcium silicate crystals ( Figure 5 ) is a spherical short fiber structure and contains a large amount of amorphous hydrated calcium silicate. The structure is dense and has limited effect on strengthening the muscles and bones of the calcium silicate board. Therefore, the flexural strength is poor and the board density is high.
[0118] It can be seen from Example 1 and Comparative Example 3 that the reaction raw materials have an important influence on the morphology of calcium silicate crystals. When diatomaceous earth is selected as the reaction raw material, the structure of the hydrothermal reaction product is as follows: Figure 6 As shown. This is because diatomite is a biogenic siliceous sedimentary rock with disordered hydrothermal active sites, so the calcium silicate crystals formed are also disordered, and no calcium silicate fibers are obtained.
[0119] It can be seen from Example 1 and Comparative Example 4 that the stirring speed has an important influence on the morphology of calcium silicate crystals. If the stirring speed is too fast, the calcium silicate fiber crystals formed will be entangled with each other and intertwined to form a hollow spherical structure ( Figure 7 ), will affect the dispersion of calcium silicate crystals in the calcium silicate board, and the mechanical properties of the board will not be significantly improved, and unnecessary energy consumption will be wasted. In addition, if the stirring rate is too low, the silicon source and calcium source are easy to sink to the bottom and accumulate, the reaction is not complete, and the product is easy to block the discharge hole, affecting the operation of the equipment.
[0120] From Example 1 ( Figure 3 ) and Comparative Example 5 ( Figure 8 ) shows that the calcium silicate fiber crystals are small in size and high in aspect ratio, and have good compatibility with the calcium silicate board, and are not easy to produce pores inside the board. However, pulp fibers are long in size and easy to absorb water, which will produce voids when filled in the calcium silicate board, resulting in a decrease in the density of the board, thereby affecting the mechanical properties of the board.
Claims
1. A method for preparing a calcium silicate board using calcium silicate fiber crystals, characterized in that: The specific steps include: (1) selecting a high-quality silicon source, a high-quality calcium source and water, mixing and stirring, and performing a hydrothermal reaction at a temperature of 200 to 240° C. and a pressure of 1.5 to 3.3 MPa; after the hydrothermal reaction is completed, the product is post-treated to obtain calcium silicate fiber crystals; in the step (1), the molar ratio of SiO2 in the high-quality silicon source to CaO in the high-quality calcium source is 1 to 1.2, and the mass ratio of the total mass of the high-quality silicon source and the high-quality calcium source to water is 1:15 to 30; (2) After mixing a common silicon source, a common calcium source, gypsum, cement, an inorganic filler and water evenly, adding calcium silicate fiber crystals, and mixing them evenly together to obtain a slurry; (3) injecting the slurry into a mold and pre-curing to obtain a pre-cured sample; then placing the pre-cured sample in a steam curing kettle for autoclave curing; after the autoclave curing is completed, drying, sanding, and cutting the steam-cured sample to obtain a calcium silicate board; In the step (1), the high-quality silicon source is white silica ash, and the mass content of SiO2 in the white silica ash is not less than 95%; In step (1), the high-quality calcium source is calcium oxide, and the purity of the calcium oxide is not less than 90%; The hydrothermal reaction time in step (1) is 3 to 6 hours, and the stirring rate is 400 to 800 rpm; In the step (3), the autoclave curing temperature is 180-200° C., the pressure is 1-1.5 MPa, and the autoclave curing time is 8-16 hours.
2. The method for preparing a calcium silicate board using calcium silicate fiber crystals according to claim 1, characterized in that: The common calcium source in step (2) is one or a combination of calcium silicate slag, carbide slag, quicklime and slaked lime.
3. The method for preparing a calcium silicate board using calcium silicate fiber crystals according to claim 1, characterized in that: In the step (2), the common silicon source is one or a combination of calcium silicate slag, microsilica powder, silicon micropowder, and quartz sand.
4. The method for preparing a calcium silicate board using calcium silicate fiber crystals according to claim 1, characterized in that: The inorganic filler in step (2) is one or a combination of diatomaceous earth, bentonite and fly ash.
5. The method for preparing a calcium silicate board using calcium silicate fiber crystals according to claim 1, characterized in that: The weight proportions of the raw material components in the step (2) are as follows, wherein the ordinary silicon source is weighed according to its SiO2 weight content, and the ordinary calcium source is weighed according to the weight content of its calcium-containing compound: 25-35 parts of SiO2 in the ordinary silicon source, 24-30 parts of calcium-containing compounds in the ordinary calcium source, 8-15 parts of gypsum, 8-15 parts of cement, 5-30 parts of calcium silicate fiber crystals, 3-8 parts of inorganic filler, and 250-500 parts of water.
6. The method for preparing a calcium silicate board using calcium silicate fiber crystals according to claim 1, characterized in that: In the step (3), the pre-curing temperature is 50-60° C. and the time is 4-8 hours.
7. A calcium silicate board prepared using calcium silicate fiber crystals, characterized in that: The calcium silicate board prepared using calcium silicate fiber crystals is prepared by the preparation method described in any one of claims 1 to 6.
Citation Information
Patent Citations
Calcium silicate board and preparation method thereof
CN113998933A
Preparation method of calcium silicate board and calcium silicate board
CN114988780A
Light-weight high-strength calcium silicate board for coating / film covering and preparation method of light-weight high-strength calcium silicate board
CN113060987A